Przeniesienie siedziby statutowej spółki do innego państwa członkowskiego w świetle swobody przedsiębiorczości - Stefanicki, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In the light of the established case-law of the Court of Justice of the European Union, all normative regulations that hinder or significantly impede the exercise of fundamental freedoms guaranteed by the Treaty are considered as limitations. Deviations from the above rule should be justified, and the restrictive measure should be appropriate to ensure the accomplishment of the adopted objective and not going beyond what is necessary to achieve it. Therefore, the question arises as to what extent the company’s personal status may be determined by the law of each Member State and how the solution in this aspect is important from the point of view of implementing business conditions
Keywords: personnel statute; transfer of registered office; freedom of establishment; national restrictions